Present situation and development prospects of the diagnosis and treatment of rotator cuff tears - Zhou, Tianjun; Han, Chang; Weng, Xisheng (Frontiers in Surgery, 2023)
Rotator cuff tears are an important cause of shoulder pain caused by degeneration or trauma of the shoulder tendon at the anatomical neck of the humeral head. The understanding and research of rotator cuff tears has a history of hundreds of years, and their etiology, diagnosis and treatment have a complete system, but some detailed rules of diagnosis and treatment still have room for development. This paper briefly introduces the diagnosis and treatment of rotator cuff tears. The current situation and its valuable research direction are described.